Polimorfismo no íntron 1-PstI do gene do hormônio do crescimento em linhagens de tilápia do Nilo (Oreochromis niloticus) - Blanck, Danielly Veloso (2008)
Molecular genetics studies are becoming more common in tilapicultura, because the Nile tilapia shows great potential in genetic engineering dedicated to the improvement stocks. With the development of different Nile tilapia (Oreochromis niloticus) strains have been increased the need to identify them, aimed the maintenance and the certification of genetic material quality of improved strains acquired by the producers. Improvement of fish natural growth rates in aquaculture has been widely explored, with gains resulting from improvements in livestock production, nutrition and genetic selection. Due to the high impact of GH in growth regulation and by being involved in several other metabolic functions, the GH gene is a potential target for genetic variation studies and its association with characteristics of fish growth. Thus, this study aimed to: describe the gene intron 1 variability of the growth hormone (GH1) of strains Chitralada and GIFT (Genetically Improvement Farmed Tilapia) from the Nile tilapia through molecular marker PCR-RFLP; study the association of this gene polymorphisms with strains performance characteristics; and seek a molecular marker that could be used in the strains identification and as a selection tool for growth characteristics in genetic improvement programs for the Nile tilapia. 200 animals were used of each strain from witch it was collected fragments of tail fin and the following measurements: total length (CT), standard length (CP), height (AL), width (LA), head length (CC), slaughter weight (PA), fillet weight (PF), fillet yield (RF) and the carcass weight (PC). From collected fin, it was done the genomic material extraction using saturated NaCl (5M). For PCR-RFLP analysis, it was necessary a specific pair of primer design based on the available sequence-reference in the GenBank (access M97766). The generated PCR products were digested with enzyme PstI, with restriction locus located in the intron of the gene GH1. Allelic frequencies, genotypic, rates of heterozygosity, test of the Hardy-Weinberg equilibrium and estatistic F were determined with Popgen 1.31 program. The analysis of the association between the polymorphisms and the performance characteristics were evaluated by the SAS GLM procedure. Duncan test (p <0.05) was used for the variables that showed effect of interaction between genotype and lineage. The three pairs of primers designed amplified satisfactorily in the two strains, producing fragments of 652, 441 and 396 bp. For 652 bp fragment, it was observed the three digestion standard possible for both strains, Chitralada and GIFT, corresponding to the genotypes PstI+/+, PstI+/- and PstI-/-. The genotypic frequencies found for the Chitralada strain were 0.707, 0.282 and 0.011 respectively for the genotypes PstI+/+, PstI+/- and PstI-/- and the GIFT strain, 0.930, 0.075 and 0.005 for the same genotypes. The allelic frequencies obtained in this study (GH1-PstI) show that the PstI+ is dominant in the Nile tilapia. The Chitralada strain (Ho = 0.282) showed greatest heterozygosity to GIFT strain (Ho = 0.065), having therefore a higher variability to the locus in question. The index of differentiation (FST) of the strains was 0.038. The allelic frequencies in the two strains were in Hardy-Weinberg equilibrium. About the association analysis of polymorphisms for production characteristics, there was no correlation only for CC and RF. So the major averages were recorded for animals that carriers the heterozygous genotype. Only to the RF characteristic there was an interaction effect between genotype and strain, to the point that the GIFT strain with homozygous genotype PstI+/+ was 2.72 percent higher than the genotype heterozygous PstI+/-. Within each genotype, the Chitralada strain was higher. With the results obtained here, it is suggested that the combination of performance characteristic of the Nile tilapia strains to the genetic polymorphisms of GH may be due to the effect of the gene regulation of growth hormone. Later detailed identifications of polymorphisms GH1-PstI structure may prove link between RFLPs described and the characteristics controlled by GH, which can contribute to the implementation of MAS in the tilapia genetic programs improvement.